Diagnostic Yield of Next-generation Sequencing in Very Early-onset Inflammatory Bowel Diseases: A Multicentre Study. (18th May 2018) - Charbit-Henrion, Fabienne; Parlato, Marianna; Hanein, Sylvain; Duclaux-Loras, Rémi; Nowak, Jan; Begue, Bernadette; Rakotobe, Sabine; Bruneau, Julie; Fourrage, Cécile; Alibeu, Olivier; Rieux-Laucat, Frédéric; Lévy, Eva; et al.
Abstract: Background and Aims: An expanding number of monogenic defects have been identified as causative of severe forms of very early-onset inflammatory bowel diseases [VEO-IBD]. The present study aimed at defining how next-generation sequencing [NGS] methods can be used to improve identification of known molecular diagnosis and to adapt treatment. Methods: A total of 207 children were recruited in 45 paediatric centres through an international collaborative network [ESPGHAN GENIUS working group] with a clinical presentation of severe VEO-IBD [ n = 185] or an anamnesis suggestive of a monogenic disorder [ n = 22]. Patients were divided at inclusion into three phenotypic subsets: predominantly small bowel inflammation, colitis with perianal lesions, and colitis only. Methods to obtain molecular diagnosis included functional tests followed by specific Sanger sequencing, custom-made targeted NGS, and in selected cases whole exome sequencing [WES] of parents-child trios. Genetic findings were validated clinically and/or functionally. Results: Molecular diagnosis was achieved in 66/207 children [32%]: 61% with small bowel inflammation, 39% with colitis and perianal lesions, and 18% with colitis only. Targeted NGS pinpointed gene mutations causative of atypical presentations, and identified large exonic copy number variations previously missed by WES. Conclusions: Our results lead us to propose an optimised diagnostic strategy to identify known monogenic causes of severe IBD.